Cost Competition, Fragmentation and Globalization - Barbara Dluhosch; Michael Burda (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper proposes a model in which the removal of barriers to trade and factor mobility is associated with endogenous fragmentation of the value-added chain. Fragmentation is the outcome of cost competition - the profit-maximizing choice of cost structure by monopolistically competitive firms. An expansion of the integrated trading area can induce globalization not only in the horizontal dimension associated with love-of-variety preferences, but also in a vertical dimension as firms vary specialization of production stages. While increased trade is likely to in-duce fragmentation when the number of firms is fixed, free entry can either reverse or intensify this result.
Keywords: 330; International trade; organization of production; technology choice; division of labor